Laser ultrasonic method for determination of crystallographic orientation of large grain metals by spatially resolved acoustic spectroscopy (SRAS) - Li, Wenqi (2012)
This thesis presents a crystallographic orientation determination technique which is based on a laser ultrasonic method: spatially resolved acoustic spectroscopy (SRAS). Surface acoustic waves (SAW) propagate on a solid surface with a phase velocity that is frequency independent, but which varies with the crystallographic orientation. By comparing the SRAS results with the calculated SAW velocities, the orientation of crystal can be determined.